Profiling and characterization of oat cultivars (Avena sativa L.) with respect to bioactive compounds, pesticide residues and mycotoxin. Issue 1 (1st January 2021) - Jiang, Guihun; Ibrahim, Muhammad Suhail; Ibrahim, Muhammad Khalid; Zhao, Chen; Butt, Madiha; Ameer, Kashif; Ahmad, Asif; Mumtaz, Amer; Anjum Murtaza, Mian; Ahmed Khalil, Anees; Asad, Muhammad Javaid; Khan, Muhammad Azam
ABSTRACT: Oat predominately cultivated as forage crop and is not explored for its value-added bioactive moieties. This study was aimed to characterize five selected oat ( Avena sativa L.) cultivars with respect to organic sugars, antioxidant activities, pesticide residues, mycotoxin and phenolic acids as measured HPLC. Five indigenous oat cultivars (Avon, PD2LV65, S2000, SGD2011, SGD81) were profiled for seven phenolic acids (gallic acid, vanillic acid, caffeic acid, syringic acid, p -coumaric acid, chlorogenic acid and ferulic acid). Highest concentrations of vanillic acid, gallic acid, caffeic acid, syringic acid, ferulic acid, p -coumaric acid and chlorogenic acid were detected in the SGD2011, SGD81, S2000, SGD2011, S2000, SGD2011 and PD2LV65 respectively. TPC in case of all oat cultivars ranged 50.88–101.56 mg/100 g. Among all oat cultivars, SGD-81 exhibited the highest DPPH activity, TPC, TFC and TFoC contents whereas, SGD-2011 showed the highest total anthocyanin content followed by AVON. S2000 showed the highest concentration of mycotoxin M1 (18.51 ppm), while lowest M1 content (10.51 ppm) were exhibited by SGD-81. Abamectin and permethrin pesticide residues were undetected in oat cultivars whereas, Dieldrin was only detected in SGD-81 and chloropyrifos was not detected in S2000 and SGD-81. Mandipropamid, parathion methyl, chlorthalonil, indoxacarb and lufernon were detected in the highest concentrations in SGD2011 and S2000 oat cultivars. Moreover, fructose, glucose and sucrose were found in highest amounts in S2000, PD2LV65 and SGD2011, respectively. Conclusively, it was evident from the results that SGD-81, SGD2011 and SG2000 could be utilized as source of important and promising phytochemicals of nutraceutical significance. Moreover, significant potential of these oat cultivars can be harnessed owing to value addition and exploitation in formulations of functional food ingredients and foodstuffs.